This is wildfire : how to protect yourself, your home, and your community in the age of heat - Mott, Nick; Angle, Justin (Bloomsbury Publishing, 2023)
"Wildfires are getting more destructive than ever before. Flames in forests are scorching about twice as many trees as they did two decades ago, and nearly 100,000 homes, barns, and other structures have been incinerated. "Fire seasons" are now fire years. Tens of millions of people live in areas vulnerable to fire, and more keep moving in. Driven in part by climate change, the areas burned and prevalence of smoke in the skies is expected to skyrocket in the decades to come. At the same time that wildfires leave swathes of the country in ash, they also renew. Wildfire is crucial for ecosystems to function and flourish. We're putting out many of the fires our landscape needs, and the ones that escape our control are devastating for forests and communities. It's clear what we're doing isn't working. Wildfire is inevitable, and we need to learn to live with it. The first of its kind, This Is Wildfire is required reading for our new reality. It offers everything you need to know about fire in one useful volume: reflects on the history of humanity's connection to flames; analyzes how our society arrived at this perilous moment; and recounts stories of those fighting fire and trying to change our relationship with it. It also offers practical advice: choosing your insurance and making your home resilient to burns; packing an emergency go-bag; rebuilding after a fire; and so much more."--Amazon.com.